Intraocular Pressure and Retinal Nerve Fibre Layer Thickness Changes After Carotid Artery Stenting - BALTACIOĞLU, FEYYAZ; MİDİ, İPEK; ERASLAN, MUHSİN (TURKISH OPHTHALMOLOGICAL SOC, 2017)
Objectives: The aim of this study was to evaluate intraocular pressure (IOP) and retinal nerve fiber layer (RNFL) changes in patients with carotid artery stenosis (CAS) after carotid artery stenting. Materials and Methods: This study was conducted as a cross-sectional, non-randomised clinical case series. Fifteen male patients (mean age: 63.6ae9.1) with CAS and more than 70% carotid artery narrowing were included. All of the patients were followed in the department of neurology and were operated in the interventional radiology division. Eighteen healthy male subjects (mean age: 63.7ae5.3) were included in the control group. All of the healthy subjects had a detailed ophthalmological examination and subjects with any chronic eye disease were excluded from the study. All of the participants had a detailed ophthalmological examination including tonometry using Goldmann applanation tonometry and RNFL analysis using optical coherence tomography (RTVue-100 5.1). Results: There were no ocular ischemic symptoms in any of the participants. The mean IOP value was 15.1ae2.1 mmHg in the control group and 16.6ae2.4 mmHg before stent implantation, 16.4ae2.2 mmHg at 1 week after implantation, 16.6ae2.5 mmHg at 1 month after implantation, and 16.7ae2.9 mmHg at 3 months after implantation in the CAS group. Mean RNFL thickness was 105ae6 mu m in the control group; in the CAS group, mean RNFL thickness values were 98ae27 mu m before stent implantation and 103ae11 mu m, 101ae10 mu m, and 101ae11 mu m at 1 week, 1 month, and 3 months after stenting. There were no significant differences between the CAS group and control group regarding IOP and RNFL thickness values (p> 0.05). IOP and RNFL thickness also did not show any statistically significant changes from preoperative measurements in 3 months postoperative follow-up in the CAS group (p> 0.05). Conclusion: IOP and RNFL thickness remained unchanged after carotid stent implantation in carotid artery stenosis patients with no signs of ocular ischemic syndrome.
Keywords: Carotid artery stenosis; stenting; color Doppler ultrasound; intraocular pressure; retinal nerve fiber layer thickness; OCULAR ISCHEMIC SYNDROME; OPEN-ANGLE GLAUCOMA; AQUEOUS-HUMOR; FLOW; CIRCULATION; STENOSIS; VESSELS